Carbon and Nitrogen Stocks in Soil under Native Pastures in the Pantanal Wetland Biome, Brazil - Freitas, Diego Antonio França de; Silva, Marx Leandro Naves; Cardoso, Evaldo Luis; Oliveira, Dener Marcio da Silva; Moitinho, Mara Regina [UNESP]; Curi, Nilton (MDPI, 2024)
The Pantanal has a high diversity of native pastures that provide food for many wild and domestic animals. Pantanal cattle raising is practiced in an extensive grazing-based system that varies according to the flood levels in the area. This study aimed to evaluate the fractions of soil organic matter in areas of native pastures under different uses and to quantify C and N stocks in sandy soils of the Pantanal. Soil samples from three native pastures differentiated by the predominance of Hymenachne amplexicaulis, Axonopus purpusii, and Mesosetum chaseae under different land use systems (continuous grazing and no grazing for five years) were collected and used to quantify the contents of carbon, nitrogen, and humic fractions. The dynamics of SOM are modified in grazed areas of the Pantanal, with influence on C and N, including their stocks. Native pastures of Axonopus purpusii and Hymenachne amplexicaulis showed an increase in organic matter after five years without grazing, while Mesosetum chaseae showed lower soil density and nitrogen levels. The highest C stock was observed in ungrazed areas of H. amplexicaulis (127.41 Mg ha−1 in the 0–40 cm layer). The dynamics of nitrogen in Pantanal pastures are influenced by the type of vegetation and land management, with higher nitrogen content in the surface layer (0–10 cm) and an increasing C/N ratio with soil depth, indicating lower nitrogen availability.
Keywords: humic fractions; soil organic matter; soil quality